If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2 + -3x = 24 + -1k Reorder the terms: -2 + x + -3x = 24 + -1k Combine like terms: x + -3x = -2x -2 + -2x = 24 + -1k Solving -2 + -2x = 24 + -1k Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -2x = 24 + 2 + -1k Combine like terms: -2 + 2 = 0 0 + -2x = 24 + 2 + -1k -2x = 24 + 2 + -1k Combine like terms: 24 + 2 = 26 -2x = 26 + -1k Divide each side by '-2'. x = -13 + 0.5k Simplifying x = -13 + 0.5k
| 4y^2+4y= | | 28+x=29 | | 25=23+a | | 1/5(y-3) | | 1/5(y-3)=t-2 | | f(x)=3x^2+1 | | -15=-10+5t | | 6y+2=82x | | 4v^2-9v+5=0 | | 6y+3x=82 | | x^2-6x+8y+41=0 | | 3/3p=15 | | 2(x+y)=14 | | 4+16=x | | 4y-x=10 | | 3a^2-7a^4=9-a^4 | | v+2/3=15/v-2 | | 6x^3-x^2+17=2x^2+47 | | 3/2p=15 | | 6(2x-3)=2(6x+2) | | 18.26+(-1.08)+0.44= | | x-.2x=68 | | 2n-(24-n)=30 | | 3(Y+X)=12 | | 3(X+Y)=12 | | 3xy+(2x-3y)=0 | | 28z-6(3z-5)=40 | | x^3-10x^2-27x-160=0 | | 2(3h+1)=20 | | 20=a^2 | | 7=a^1 | | 3(20)+35= |